THE EFFECTIVENESS AND CHALLENGES OF ONLINE LEARNING (Konferensiyalar | Conferences, 2024)
Online learning is spreading all over the world. Exploring the realm of virtual education unveils both its promising effectiveness and challenges that it presents. In this article delves into the dynamic landscape of online learning, examining its efficacy in facilitating education while also navigating the obstacles it poses. This article is a collection of necessary information about online learning using by the articles, as well as, it serves as a comprehensive resource on the topic.